The global covenant human conduct in a world of states - Jackson, Robert H. (Oxford : Oxford University Press, 2000)
Jackson examines international relations and brings it into contact with the new era of world politics. He presents an analysis of important international issues including peace and security, war and intervention, human rights and democracy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: International relations; International organization; World politics -- 1989-